2012
DOI: 10.4028/www.scientific.net/amr.524-527.953
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Characteristics and Desilicon Ability of 10 Strains of Silicate Bacteria Screened from Different Bauxite Ores

Abstract: Ten strains of silicate bacteria were screened from three bauxite samples in Jiangxi Province and Henan Province in China. The ten strains were determined as B. mucilaginosus according to the results of physiological and biochemical characteristics and desilicon ability. Bioleaching tests showed that the ten strains all can decompose bauxite ore and release silicon from bauxite, but had a large difference of desilicon ability among them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…This inoculant can release the K present in stable soil minerals through chelation, complexolysis, exchange reactions, acidolysis, and organic acid production. It also releases other minerals present in the soil, such as Si, Fe, and Ca [ 14 , 17 ]. Han (2006) found that the KSB inoculant, when applied to soil, had a positive effect on the uptake of potassium in a variety of crops, including cotton, cucumbers, and oilseed rape [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…This inoculant can release the K present in stable soil minerals through chelation, complexolysis, exchange reactions, acidolysis, and organic acid production. It also releases other minerals present in the soil, such as Si, Fe, and Ca [ 14 , 17 ]. Han (2006) found that the KSB inoculant, when applied to soil, had a positive effect on the uptake of potassium in a variety of crops, including cotton, cucumbers, and oilseed rape [ 18 ].…”
Section: Introductionmentioning
confidence: 99%